Review paper Interleukin 18 – a pleiotropic cytokine involved in the Th1 and Th2 immunological response - Trzeciak, Magdalena; Sokołowska-Wojdyło, Małgorzata; Barańska-Rybak, Wioletta; Maciejewska, Agata; Michajłowski, Igor; Roszkiewicz, Jadwiga (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Interleukin 18 (IL-18) is a pleiotropic cytokine that plays a crucial role in the control of the balance between the Th1 and Th2 response. Synergistically with IL-12, IL-18 promotes an immunological response of the TH1 type, by enhancing INF-γ synthesis and inhibition of IgE production. On the other hand, IL-18 can enhance IL-4 and IL-13 production and stimulates IgE synthesis. Moreover, in the presence of IL-3, IL-18 can directly stimulate basophils and mast cells to produce their mediators. The gene of IL-18 is located on chromosome 11q22.2-22.3, which was identified as an important candidate region for susceptibility to atopy. The aim of this paper is to characterize IL-18, the evolution of views on it and to emphasize the influence of IL-18 on the development of infectious, inflammatory, autoimmune diseases and malignancies with a special consideration of atopic diseases.